2019
DOI: 10.1038/s41419-019-1574-5
|View full text |Cite
|
Sign up to set email alerts
|

FSCN1 is an effective marker of poor prognosis and a potential therapeutic target in human tongue squamous cell carcinoma

Abstract: To estimate the value of FSCN1 in evaluating the prognosis and guiding the targeted therapy for patients with tongue squamous cell carcinoma (TSCC). Using the Oncomine database, we found some genes especially FSCN1 differentially expressed between TSCC samples and tongue normal samples. So we compared FSCN1 expression between TSCC and normal cell lines and knocked down FSCN1 in TSCC cells to observe its influence on the viability and trans-migration in vitro and tumor growth in vivo. Then we measured FSCN1 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 34 publications
(54 reference statements)
1
21
0
Order By: Relevance
“…20 Out of 131 samples of OSCC studied by Alam et al, only 74.80% of the cases showed fascin staining while it was not detected in 25.19% of the cases. 26 In a study by Chen et al in 106 cases of tongue 26,27 In our study, fascin expression seems to be increasing from well to moderate to poor OSCC (Table 3 and Fig. 5).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…20 Out of 131 samples of OSCC studied by Alam et al, only 74.80% of the cases showed fascin staining while it was not detected in 25.19% of the cases. 26 In a study by Chen et al in 106 cases of tongue 26,27 In our study, fascin expression seems to be increasing from well to moderate to poor OSCC (Table 3 and Fig. 5).…”
Section: Discussionsupporting
confidence: 61%
“…Comparison of fascin expression patterns in NOM and OED (Tukey's post hoc test) 2% of cases exhibited high fascin expression, while 34.9% of cases showed relatively low fascin 27. This disparity of fascin immunoreactivity between studies could be attributed to the difference in sample size, the methods of evaluation of staining, or technical errors.…”
mentioning
confidence: 99%
“…[30][31][32] FSCN1 has been reported to support the invasion and metastasis of various cancer cells. [33][34][35] In this study, HBEGF and FSCN1 were also shown to be potential targets for SOX2 in breast cancer. Ectopic expression of SOX2 upregulated HBEGF and FSCN1 expression, and SOX2 knockdown reduced the expression of HBEGF and FSCN1.…”
Section: Discussionmentioning
confidence: 63%
“…FSCN1 is a member of the fascin family of actin-binding proteins, and regulates cellular migration, motility, adhesion, and inter-cellular interactions [ 37 ]. The oncogenic role of FSCN1 has been described in multiple cancers including ESCC [ 24 , 38 – 40 ]. FSCN1 is targeted by multiple lncRNA-miRNA pairs in ESCC such as PVT1-miR-145, TTN-AS1-miR-133, and ROR-miR-145 [ 41 – 43 ].…”
Section: Discussionmentioning
confidence: 99%